Sustainability and sustainability communication of pharma industry companies located in Finland - Sirkko, Hannamari (2023)
Sustainability is an important part of business environment as responsible behaviour is expected from companies in the dimensions of environment, social and business. Even though there are no commonly accepted definition for the phenomenon, companies are involved to it and taking actions to meet the expectations of stakeholders. Strategic communication aims to maintain the healthy reputation of the organisation in the eyes of the public and to advance the mission of the organisation. Through strategic communication on sustainability related issues, companies might obtain the benefits from their responsible behaviour and to enhance the relationship and trust with stakeholder groups.